(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
In 2022, 2.3 million women worldwide were diagnosed with breast cancer, resulting in 670,000 deaths. This type of cancer occurs in women of all ages after puberty, and the risk of developing it increases with age. Interestingly, the prevalence and mortality of breast cancer vary greatly depending on the country’s level of development. For example, in highly developed countries, one in twelve women will experience this condition in their lifetime, and one in 71 will die from it.